Peer attachment, self-efficacy and aggression among secondary school adolescents in Selangor, Malaysia - Choy, Chiau Wei; Madon, Zainal (Universiti Putra Malaysia Press, 2019)
The present study investigated the relationships between peer attachment, self-efficacy and aggression among early adolescents. Furthermore, this study examined the mediating role of self-efficacy on the relationship between peers attachment and aggression among early adolescents. A total of 471 early adolescents aged 14 were selected from eight selected secondary schools in Selangor, Malaysia, recruited using multistage cluster sampling method. The questionnaires consisted of the revised version of the Inventory of Parent and Peer Attachment (IPPA), Self-Efficacy Questionnaire for Children (SEQ-C) and Reactive-Proactive Aggression Questionnaire (RPQ). The results revealed that there was significant negative relationships between peer attachment, self-efficacy and early adolescent's aggression. Additionally, the result also showed that peer attachment had an indirect effect on aggression via self-efficacy. Evidently, the relationship between peer attachment and aggression among early adolescents was fully mediated by self-efficacy. Self-efficacy and peers attachment play important roles in the development of aggression among early adolescents. Practical recommendations are discussed and those factors should be taken into consideration to implement the interventions in curbing aggression among early adolescents in Malaysia.